MEDU-23. IMPROVING IMMUNOTHERAPEUTIC POTENTIAL IN GROUP 3 MEDULLOBLASTOMA USING LOW DOSE RADIATION FOLLOWED BY 4-1BB MONOCLONAL ANTIBODY ADMINISTRATION. (23rd April 2019) - Alshareef, Mohammed; Eskandari, Ramin; McDonald, Daniel; Vanek, Kenneth; Jenrette, Joseph; Patel, Sunil; Cheshier, Samuel; Cachia, David; Das, Arabinda
Abstract: INTRODUCTION: Group 3 Medulloblastoma (MB) subtype has the worst prognosis amongst the MB subtypes. Despite aggressive treatments, survival of patients with Group 3 MB remains below 50% over 5 years. A limitation of therapeutic success is cancer cellular mechanisms suppressing immune responses, enabling escape of detection. We previously identified tumor-associated micoglias (TAMs) as important in T-cell-excluded tumor phenotype. The goal of our study was to reprogram intratumoral TAMs to allow T-cell infiltration into Group 3 MB tumor, improving efficacy of immunotherapy. We examine the immunobiologic rationale for treating with low-dose radiation treatment (LDRT) followed by 4-1BB monoclonal antibody (mAB) treatment. METHODS: Brain tissue was obtained from patients with Group 3 MB at MUSC and Group 3 MB cell line MP1 and were implanted over the occipital bone in C57BL/J mice. We examine treatment with 1 Gy LDRT followed by 4-1BB-targeting mAB and evaluate conversion of M2 microglia into the M1 phenotype, enhancement of MB cell death in ex vivo human and mice. We evaluate post-treatment tumoral size, cell death, and survival in mice. RESULTS: TAMs were activated with LDRT followed by 4-1BB antibody and converted from M2-like to M1-like microglia. Total number of tumor infiltrate leukocytes (TILs) following treatment was significantly increased. In vivo mice models reacted similarly, with increased tumoral cell death in response to LDRT and 4-1BB mAb. There was reduction of tumor size by 60% and increased survival when compared to untreated controls. We also determined that cell death occurred within malignant tumor cells but not healthy neuronal cells following LDRT plus 4-1BB mAb treatment. CONCLUSIONS: We propose a novel treatment using LDRT followed by 4-1BB antibody to increase TAMs activation, conversion of T-cells and result in significant increase in intra-tumoral cell death, reduction in in vivo tumor size and increased overall survival in a mouse model.